Assessing the dimensional accuracy of the resultant casts made from monophase, one-step, two-step, and a novel two-step putty light body impression technique - An in vitro study - Harini K ShivaKumar; Supriya Manvi; Ulhas N Amasi; Sounyala Rayannavar (Wolters Kluwer Medknow Publications, 2020)
Background: The clinical success of fixed prosthodontics and dental implants is dependent on the dimensional accuracy of the impression obtained. Although there are many studies on different impression materials and the accuracy of the dies, only a few studies on the techniques of impression making hence this study was taken to evaluate and compare the dimensional accuracy of casts made from four different impression techniques. Aim: This study aims to assess the dimensional accuracy of the resultant casts made from a monophase, one-step, two-step, and novel two-step putty light body impression technique. Settings and Design: An in vitro study. Materials and Methods: A stainless steel model of two abutments with specific distance was fabricated. An impression of this model was made with four different impression techniques using a polyvinyl siloxane impression material using custom made trays. Ten impressions were made with each impression technique. Total 40 impressions made and casts poured with type IV gypsum, and accuracy of the casts measured using a traveling microscope. Three dimensions, i.e., diameter, height, and inter-abutment distance measurements were obtained. Statistical Analysis: The statistical analysis was done using one-way ANOVA and Student Newman-Keuls test. Results and Conclusion: The casts obtained from all four techniques had significant differences in dimensions as compared to that of the master model. The order for highest to lowest accuracy from, the stainless steel model was; monophase < one-step < two-step < two-step injection technique. The two-step and two-step injection techniques produced the most accurate cast, with the two-step injection technique performance being better than the two-step technique casts obtained.